The presence of amphibians and reptiles in the Golija Mountain compared with fauna of other areas - Ajtić Rastko D.; Nikolić Sonja Z.; Simović Aleksandar B.; Ćirković Glorija Ž. (Kragujevac Journal of Science)
Batracho- and herpetofauna of the Golija Mountain have not yet been sufficiently explored. During nine years of research, a total of 22 species of amphibians and reptiles were recorded in the Nature Park "Golija", and in the area of the "GolijaStudenica" Biosphere Reserve, which comprises 45.83% of all autochthonous amphibians and reptiles in Serbia. The presence of the species was ascertained by direct or indirect observation. Some species were recorded for the first time. Most species have the status of strictly protected. Sorensen's similarity coefficient had high values between Golija Mt. and all compared areas. The presented data are not final, but they significantly contribute to the knowledge of the fauna of these areas. It is necessary to establish long-term research and a system of active or passive monitoring.